High electrocatalytic performance of a graphene-supported PtAu nanoalloy for methanol oxidation. (12th July 2018) - Chang, Gang; Cai, Zhiwei; Jia, Hongmei; Zhang, Zaoli; Liu, Xiong; Liu, Zhihua; Zhu, Ruizhi; He, Yunbin
Abstract: Homogeneously distributed PtAu nanoalloy anchored to graphene (PtAuNA/G) was synthesized via a simple one-step electrochemical deposition process, in which Pt and Au ions and graphene oxide was simultaneously electro-reduced on the glassy carbon electrode. The morphology evolution of PtAuNA/G synthesized with different deposition times was characterized via field-emission scanning electron microscopy. X-ray diffraction and transmission electron microscopy was applied to confirm the alloy structure. The electrodeposition conditions, including the deposition time, were further optimized to explore the morphological evolution of PtAuNA/G. Based on cyclic voltammetry and chronoamperometry results, it was found that PtAuNA/G can efficiently catalyze the oxidation of methanol in alkaline media with dramatically enhanced electrocatalytic activity (7.268 mA cm −2, 3.83 times higher than that of commercial carbon-supported Pt nanoparticles, 1.894 mA cm −2 ), along with a considerably improved tolerance to poisoning (current decline: 69% vs 99.89%). These results indicate a great potential for PtAuNA/G in fabricating high-performance direct methanol fuel cells. Highlights: PtAu nanoalloys on graphene were synthesized via simple electrodeposition. Electrocatalytic properties of PtAuNA/G can be tuned by changing the electrodeposition time. PtAuNA/G shows much enhanced electrocatalytic activity for methanol oxidation. Its electrocatalytic activity is 3.84 times that of commercial electrocatalyst (Pt/C). PtAuNA/G shows also superior poison resistance in methanol oxidation process.